Advertisement Remove all ads

Factorise: (6 2/3)^2 - (2 1/3)^2 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

Factorise: `(6 2/3)^2 - (2 1/3)^2`

Advertisement Remove all ads

Solution

`(6 2/3)^2 - (2 1/3)^2`

`= (20/3)^2 - (7/3)^2`

`= (20/3 + 7/3)(20/3 - 7/3)`

`= (27/3)(13/3) = 9 xx 13/3 = 39`

Concept: Factorisation by Difference of Two Squares
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 13 Factorisation
Exercise 13 (C) | Q 13 | Page 159
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×